2013
DOI: 10.1371/journal.pone.0070731
|View full text |Cite
|
Sign up to set email alerts
|

IVIg Treatment Reduces Catalytic Antibody Titers of Renal Transplanted Patients

Abstract: Catalytic antibodies are immunoglobulins endowed with enzymatic activity. Catalytic IgG has been reported in several human autoimmune and inflammatory diseases. In particular, low levels of catalytic IgG have been proposed as a prognostic marker for chronic allograft rejection in patients undergoing kidney transplant. Kidney allograft is a treatment of choice for patients with end-stage renal failure. Intravenous immunoglobulins, a therapeutic pool of human IgG, is used in patients with donor-specific antibodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…A specific assessment of the effects of steroids on the levels of catalytic IgG was not possible, since all patients were administered with at least one form of steroid. Of note, in a previous analysis using the same patients cohort (16), we showed that the decrease in levels of catalytic IgG was greater in the case of patients who were treated with repeated doses of IVIg post-transplant. We had proposed that the further reduction of catalytic IgG in IVIg-treated patients could result either from a dilution of the patients’ IgG by the administered IVIg or from a direct immunomodulatory effect of IVIg on the patients’ immune system (16).…”
Section: Discussionmentioning
confidence: 57%
“…A specific assessment of the effects of steroids on the levels of catalytic IgG was not possible, since all patients were administered with at least one form of steroid. Of note, in a previous analysis using the same patients cohort (16), we showed that the decrease in levels of catalytic IgG was greater in the case of patients who were treated with repeated doses of IVIg post-transplant. We had proposed that the further reduction of catalytic IgG in IVIg-treated patients could result either from a dilution of the patients’ IgG by the administered IVIg or from a direct immunomodulatory effect of IVIg on the patients’ immune system (16).…”
Section: Discussionmentioning
confidence: 57%
“…This hypothesis is currently under evaluation in the prospective CATAPULT study. More recently, the same group showed that the levels of catalytic antibodies were heterogenous between renal transplanted patients (5). These levels drastically drop following transplantation and then slowly return to pre-transplant values, suggesting that this parameter is an intrinsic property of each individual's immune system (5).…”
Section: Structure and Function Of Antibodiesmentioning
confidence: 99%
“…This was followed by immediate size-exclusion chromatography on a superose-12 column equilibrated with 50 mM Tris, 8 M urea, and 0.02 % NaN 3 (pH 7.7) to exclude potentially contaminating proteases, as detailed in our previous reports (6,10,28). IgG-containing fractions were then pooled and dialyzed against PBS-0.02% NaN 3 for 2 days with four changes of buffer at 4°C, followed by dialysis against catalytic buffer containing 5 mM CaCl 2 (pH 7.7) for 1 day with two buffer changes at 4°C, as previously described (32). The purity of IgG preparations was confirmed by SDS-PAGE and immunoblotting under non-reducing conditions.…”
Section: Purification Of Iggmentioning
confidence: 99%
“…The purity of IgG preparations was confirmed by SDS-PAGE and immunoblotting under non-reducing conditions. IgG was quantified by ultraviolet spectrophotometry (32).…”
Section: Purification Of Iggmentioning
confidence: 99%
See 1 more Smart Citation